EFEK KOMITMEN ORGANISASI, KOMUNIKASI, LINGKUNGAN KERJA FISIK TERHADAP PRODUKTIVITAS KERJA KARYAWAN PADA APARTEMEN X JAKARTA - Didin Hikmah Perkasa; Dinar Nur Affini; Fatchuri Fatchuri (Universitas Budi Luhur, 2022)
This research was conducted to determine the effect of organizational commitment, communication and physical work environment on work productivity. The object of this research is the employees at apartment X Jakarta as many as 54 respondents using quantitative descriptive methods. Therefore, the data analysis used is statistical analysis in the form of multiple linear regression test. The results of this study indicate that partially and simultaneously, the variables of organizational commitment, organizational communication and physical work environment affect the work productivity of employees in Apartment X Jakarta. This is evidenced by the results of the simultaneous F test (F test) and the partial test results (t test) which also show significant values of the three independent variables that support the hypothesis. Therefore, the test results of this study state that there is a simultaneous influence between the variables of organizational commitment, organizational communication and the physical work environment that affect work productivity at Apartment X Jakarta.